Effect of resistance training volume on body adiposity, metabolic risk, and inflammation in postmenopausal and older females: Systematic review and meta-analysis of randomized controlled trials - Paulo Ricardo Prado Nunes; Pâmela Castro-; Anselmo Alves de Oliveira; Bruno de Freitas Camilo; Gislaine Cristina-Souza; Lucio Marques Vieira-Souza; Marcelo Augusto da Silva Carneiro (Elsevier, 2024)
Purpose: This meta-analytical study aimed to explore the effects of resistance training (RT) volume on body adiposity, metabolic risk, and inflammation in postmenopausal and older females. Methods: A systematic search was performed for randomized controlled trials in PubMed, Scopus, Web of Science, and SciELO. Randomized controlled trials with postmenopausal and older females that compared RT effects on body adiposity, metabolic risk, and inflammation with a control group (CG) were included. Independent reviewers selected the studies, extracted the data, and performed the risk of bias and certainty of the evidence (Grading of Recommendations, Assessment, Development, and Evaluation (GRADE)) evaluations. Total body and abdominal adiposity, blood lipids, glucose, and C-reactive protein were included for meta-analysis. A random-effects model, standardized mean difference (Hedges' g), and 95% confidence interval (95%CI) were used for meta-analysis. Results: Twenty randomized controlled trials (overall risk of bias: some concerns; GRADE: low to very low) with overweight/obese postmenopausal and older females were included. RT groups were divided into low-volume RT (LVRT, ∼44 sets/week) and high-volume RT (HVRT, ∼77 sets/week). Both RT groups presented improved body adiposity, metabolic risk, and inflammation when compared to CG. However, HVRT demonstrated higher effect sizes than LVRT for glucose (HVRT = -1.19; 95%CI: -1.63 to -0.74; LVRT = -0.78; 95%CI:-1.15 to -0.41) and C-reactive protein (HVRT = -1.00; 95%CI: -1.32 to -0.67; LVRT = -0.34; 95%CI, -0.63 to -0.04)) when compared to CG. Conclusion: Compared to CG, HVRT protocols elicit greater improvements in metabolic risk and inflammation outcomes than LVRT in overweight/obese postmenopausal and older females.